Raymond G. Carroll papers - Carroll, Raymond G., 1876?-1943.
Chiefly scrapbooks containing clippings of Carroll's articles for the New York Evening Post, Philadelphia Public Ledger, and the Times of London, Eng., and for other newspapers in Illinois, Missouri, and Ohio. Also includes correspondence, printed material, photographs, and drawings.
Journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: New York post; Times (London, England); American newspapers -- Illinois; American newspapers -- Missouri; American newspapers -- Ohio; American newspapers -- New York (State) -- New York; American newspapers -- Pennsylvania -- Philadelphia; English newspapers -- England -- London; Journalism -- England; Journalism -- United States; Newspapers -- England -- London; Philadelphia public ledger; Journalists